Eco-Cultural Tourism and Socio-Economic Development: A Case Study of Chandubi Festival of Chandubi Area in South Kamrup, Assam - Das, Dr. Satyajit (RA Journal of Applied Research, 2021)
Eco-Cultural Tourism is a new area which emphasizes on the promotion and development of culturally rich and ecologically important sites and locations or places. Through the promotion of this kind of tourism, the inhabitants living in the surrounding and peripheral areas may be socio-economically benefited. The community participation process would have also continued in this eco-cultural tourism. In eco-cultural tourism, the emphasis should be given on conservation of ecological diversity and cultural heritage of the respective community. In eco-cultural tourism, tourists are attracted towards the local culture and flora and fauna constituting the ecology. Chandubi is a well-known natural lake located 64 km away from the Guwahati city and included in the Rabha Hasong Autonomous Council area of south kamrup region, Assam. Chandubi Festival has been organized at the bank of the Chandubi Lake for the last 4-5 years. It is a promotional festival for attraction of visitors and tourists to Chandubi. But most prominent objective of Chandubi Festival is to create awareness among the mass for conservation of ecological diversity of the lake as well as to promote folk culture and ethnic tradition of the different communities especially of the Pati Rabha community for domestic and foreign tourists at this place. Through organizing this festival, the organizer tries to draw the attention of the concerned Departments of Government and Non-Government organizations for infrastructural development of the place and the attainment of socio-economic development of the entire community who have been participated in the different process in the promotion of eco-cultural tourism.